EUPHEMISTIC REPLACEMENT AS COMMUNICATIVE STRATEGY IN THE NEWS MEDIA - Paronyan, Shushanik; Barseghyan, Gevorg (Armenian Folia Anglistika, 2023)
In the modern era of mass media, news reports spread at an unprecedented speed, enabling people worldwide to get informed about current events. Despite the positive results of keeping media audience updated, in some complicated political situations, the ease at which news stories are formulated and made public may aggravate tension, harming the processes of political regulation or negotiation. In view of this, the use of unbiased and inoffensive language of news reporting is of paramount importance. Hence, the aim of the present research is to study the communicative strategy of mitigating meaning via euphemistic replacement in the news media. It is assumed that by replacing the informative units that nominate or describe dramatic and disastrous events with their euphemistic substitutes, the negative effect of the content can be minimised. The research is carried out on the material of articles distributed online by the media company Politico. The topic of the articles covers the dramatic humanitarian crisis in Artsakh (Nagorno Karabah region). The contextual analysis of the practical material is carried out from pragma-stylistic perspective. Euphemism is viewed not only as a figure of speech which serves a social regulatory function in the news media, but also as a tactical tool which pursues the communicative strategy of mitigating sensitive information and creating implied contextual meaning. The communicative-pragmatic study of the language data enables to conclude that euphemistic substitution is an effective communicative strategy aimed at maintaining a neutral stance on the conflict news stories and imparting implicit meaning.